Why a focus on 'what is educational?' matters so much in reconstructing education? - Whitehead, Jack; Huxtable, Marie (Irish educational studies, 2025)
This paper offers an argument as to why a focus on 'What is educational?' matters so much in reconstructing education. Living Educational Theory Research is presented as an approach that enables professional, educational-practitioners to contribute to reconstructing education locally and globally. The research is focused on the generation and testing the validity of living-educational-theories through researching questions of the kind, 'How do I improve my professional practice in education?' Living Educational Theory Research is a form of professional practitioner, self-study educational research. A living-educational-theory is an individual's explanation of their educational influence in their own learning, in the learning of others and in the learning of the social formation within which the practice is located. Research accounts are subjected to the mutual rational control of critical discussion with peers. This criticism strengthens the research, by enhancing the validity of the knowledge claims. It contributes to the reconstruction of education using an educational lens in determining what matters in reconstructing education. This extends the idea that education is focused on the transmission of knowledge. It extends it by including the knowledge-creating capacities of each individual. The conclusions concern the importance of an 'educational' lens in understanding what matters in reconstructing education.